The Inter-Divisional Communications Framework Applied to a Case Study of Inward Foreign Direct Investment Promotion in Jiaxing, China. - Mack, Stuart M A (2010)
The purpose of this study is two-fold; to contribute to the academia concerning communications models and frameworks by creating and validating a new Inter-Divisional Communications Framework, utilising past models and current practitioner insight. The second is to apply the new communications framework to a current ‘real-life’ business challenge; this is in the form of a case study auditing the communications strategy of Jiaxing (a third tier city neighbouring Shanghai). The city is currently attempting to promote inward foreign direct investment (FDI) opportunities to foreign businesses in the UK, Europe and Greece. The challenge for the city is that it has relatively little experience in communicating with foreign cultures and in promoting itself to the global community. The globalisation of business markets has heightened competition between cities for FDI (Jacobsen:2009) and it is argued that cities are becoming the key nodes of the global economy (MCI: 2009). Thus effective communication to promote awareness of an individual city is essential to surviving and competing in this global landscape. The data for the creation of the new communications model has been collated through interviews sourced through personal contacts to provide practitioner insight to direct changes to the model formed directly from previous communications theory. Since the area of ‘city image’ is a new concept in communications theory the data collation method to analyse Jiaxing’s strategy is non-standard and broad in its attempt to cover all of the channels utilised to form an overall picture of the strengths and weaknesses or efficacy of the city’s communication strategy. This study concludes that despite the relevant albeit slightly confused content of Jiaxing’s promotional message concerning FDI promotion; there is a major imbalance between the optimal target audience and those that are actually receiving the message. These key issues have been underpinned and directed by the Inter-Divisional Communications model which has emerged as a tool to better understand where further research should be conducted in order to improve the efficacy of the city’s promotional strategy.